Task-Irrelevant Visual Forms Facilitate Covert and Overt Spatial Selection - Bogadhi, Amarender R.; Buonocore, Antimo; Hafed, Ziad M. (The Journal of neuroscience, 2020)
Covert and overt spatial selection behaviors are guided by both visual saliency maps derived from early visual features as well as priority maps reflecting high-level cognitive factors. However, whether mid-level perceptual processes associated with visual form recognition contribute to covert and overt spatial selection behaviors remains unclear. We hypothesized that if peripheral visual forms contribute to spatial selection behaviors, then they should do so even when the visual forms are task-irrelevant. We tested this hypothesis in male and female human subjects as well as in male macaque monkeys performing a visual detection task. In this task, subjects reported the detection of a suprathreshold target spot presented on top of one of two peripheral images, and they did so with either a speeded manual button press (humans) or a speeded saccadic eye movement response (humans and monkeys). Crucially, the two images, one with a visual form and the other with a partially phase-scrambled visual form, were completely irrelevant to the task. In both manual (covert) and oculomotor (overt) response modalities, and in both humans and monkeys, response times were faster when the target was congruent with a visual form than when it was incongruent. Importantly, incongruent targets were associated with almost all errors, suggesting that forms automatically captured selection behaviors. These findings demonstrate that mid-level perceptual processes associated with visual form recognition contribute to covert and overt spatial selection. This indicates that neural circuits associated with target selection, such as the superior colliculus, may have privileged access to visual form information. SIGNIFICANCE STATEMENT Spatial selection of visual information either with (overt) or without (covert) foveating eye movements is critical to primate behavior. However, it is still not clear whether spatial maps in sensorimotor regions known to guide overt and covert spatial selection are influenced by peripheral visual forms. We probed the ability of humans and monkeys to perform overt and covert target selection in the presence of spatially congruent or incongruent visual forms. Even when completely task-irrelevant, images of visual objects had a dramatic effect on target selection, acting much like spatial cues used in spatial attention tasks. Our results demonstrate that traditional brain circuits for orienting behaviors, such as the superior colliculus, likely have privileged access to visual object representations.